The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23116263
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Alleviates High-Fat Diet-Induced Disruptionof Hepatic Lipid and Iron Homeostasis in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by excessive fat deposition in the liver, which is often associated with disrupted iron homeostasis. Betaine has been reported to be hepatoprotective, yet whether and how betaine ameliorates high-fat diet-induced disruption of hepatic lipid and iron homeostasis remains elusive. In this study, mice were fed either standard (CON) or high-fat diet (HFD) for 9 weeks to establish a NAFLD model. Mice raised on HF diet were then assigned randomly to HF and HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…But, BHMT protein levels were not changed in this study. There is a report that BHMT protein was also proportionally decreased linked to mRNA levels in high-fat-diet fed mouse 37 . As another possibility that BHMT protein levels did not reflect mRNA levels, Smek2 dysfunction may affect BHMT protein regulation in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…But, BHMT protein levels were not changed in this study. There is a report that BHMT protein was also proportionally decreased linked to mRNA levels in high-fat-diet fed mouse 37 . As another possibility that BHMT protein levels did not reflect mRNA levels, Smek2 dysfunction may affect BHMT protein regulation in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study showed that betaine reduces the disruption of hepatic lipid and iron homeostasis caused by a high-fat diet in mice. 46 Another study showed that betaine could alleviate liver damage caused by ionizing radiation. 47 As a functional food or pharmaceutical formulation, effervescent tablets can be used as a new formulation for patients who have difficulty swallowing ordinary tablets or capsules, and can also be improved by adding sweeteners to improve the taste.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial of 191 patients with NASH revealed that betaine supplementation for 8 weeks reduced hepatic steatosis by 25%, and liver biopsy after 12 months of treatment confirmed that betaine prevented worsening of steatosis in 55 patients with NASH (Chen et al, 2016). Betaine treatment of high‐fat diet‐induced ApoE−/− mice resulted in a significant reduction in white fat; HFD‐fed mice showed a significant reduction in the adipogenic genes PPARγ and CD36 (Li, Jiang, et al, 2022). In a mouse model of NAFLD, betaine significantly increased AMPK expression while inhibiting downstream lipid synthesis related genes; it also increased FGF10 secretion and decreased CPT1A protein expression—thus preventing NAFLD by reducing lipid synthesis and improving fatty acid oxidation (Chen, Zhang, et al, 2021).…”
Section: The Use Of Natural Products In the Treatment Of Nafldmentioning
confidence: 99%